Shared decision‐making for older adults with cardiovascular disease - Backman, Warren D.; Levine, Sharon A.; Wenger, Nanette K.; Harold, John Gordon (Clinical cardiology (Mahwah, N.J.), 2020)
Shared decision‐making is appropriate for clinical decisions involving multiple reasonable options, which occur frequently in the cardiovascular care of older adults. The process includes the communication of relevant factual information between the patient and the clinician, elicitation of patient preferences, and a mutual agreement on the best course of action to meet the patient's personal goals. For older adults, there are common challenges and considerations with regard to shared decision‐making, some of which (eg, cognitive impairment) may be biologically linked to cardiovascular disease. There are tools designed to facilitate the shared decision‐making process, known as decision aids, which are broadly effective although have shortcomings when applied to older adults. Novel approaches in clinical research and health systems changes will go some way toward improving shared decision‐making for older adults, but the greatest scope for improvement may be within the grass roots areas of communication skills, interdisciplinary teamwork, and simply asking our patients what matters most.